Russian Case Phenomena in the Polish Audience of Russian Students - Домбровский, Тадеуш (Didactics of the Russian language and the problems of translation for a foreign audience, 2020)
The effectiveness of foreign students studying the Russian language is determined by the degree of understanding of Russian speech in all its manifestations. Education also involves introducing students to the background knowledge of Russians. The author shares her experience in developing cultural literacy among students. In particular, the precedent phenomenon is considered as a carrier of cultural information of the people. The article presents the classification and characterization of case phenomena, provides examples of the source and the transformed text.